Biosignals to Detect the Imbalance of Explicit and Implicit Affect in Dementia: A Pilot Study. Issue 7 (November 2019) - Han, Doug Hyun; Ga, Hyuk; Kim, Sun Mi; Kim, Soyoung; Chang, Joon Seok; Jang, Sunghyuk; Lee, Sang Hoon
Background: We assessed implicit and explicit emotion in older patients with dementia using biosignals. Methods: Fifty patients with dementia and 34 healthy individuals watched 3 videos that aimed to elicit various emotional responses. Electroencephalogram and heart rate variability were recorded. Results: Patients with dementia experienced less fun and more fear than controls. The high frequency (HF) from the baseline in response to funny stimulation as well as HF from neutral to fear stimulation in the dementia group increased further than in the control group. The slow wave (SW)–fast wave (FW) ratio from neutral to funny stimulation in the control group increased further than in the dementia group. The SW-FW from neutral to fear stimulation was further decreased in the dementia group than in the control group. Conclusions: Although patients with dementia were more sensitive to implicit affect, they showed more enhanced imbalance between positive and negative affect in explicit affect assessment.